"Damming the Swamping Problem, Reliably". (21st April 2013) - Bates, Jared
Abstract The swamping problem is the problem of explaining why reliabilist knowledge (reliable true belief) has greater value than mere true belief. Swamping problem advocates see the lack of a solution to the swamping problem (i.e., the lack of a value‐difference between reliabilist knowledge and mere true belief) as grounds for rejecting reliabilism. My aims here are (i) to specify clear requirements for a solution to the swamping problem that are as congenial to reliabilism's critics as possible, (ii) to clear away various existing reliabilist solutions on the basis of these requirements, and (iii) to present a reliabilist solution that succeeds in meeting all of them. To meet all the requirements, my solution develops a more nuanced understanding of the epistemic end than is currently discussed, and with it a novel way of individuating beliefs. I close with a brief discussion of the question whether reliabilism's critics might impose further demands which reliabilism cannot possibly meet.